Switzerland : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Switzerland. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that the Swiss economy has adjusted to the large cumulative exchange rate appreciation that took place since the global financial crisis. After a subdued start to 2017, GDP growth accelerated to 1.1 percent in 2017, and the positive momentum continued in Q1:2018, although at a slightly reduced pace. The improved external outlook, together with the depreciation since mid-2017, are expected to energize the economy and lift GDP growth to 2.25 percent in 2018, before it gradually moderates to 1.75 percent over the medium term. Inflation is expected to increase to the upper half of the target band in 2018-19, and to subsequently revert to the mid-point.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet